Can psychological risk factors for coronary heart disease predict extent and severity of coronary atherosclerosis? - Marušič, Andrej (Zdravstveno varstvo, 2003)
Objective: The main objective of the present study was to test prediction of angiographically determined coronary atherosclerosis on the basis of presence of various psychological and other coronary risk factors. Methods: The sample constituted 176 male patients with coronary heart disease (CHD) who underwent coronary angiography. Exploratory variables consisted of psychological (personality traits of neuroticism and sensitisation, and emotional coping style) and other coronary risk factors (age, family history, smoking, hypertension, total, LDL and HDL cholesterol). Outcome variables of the study were extent score of disease and severity score of disease. The goal of statistical analysis was to find best fitting multivariate linear models. Results: Both final models included only LDL and age. Psychological risk factors did not contribute significantly to the prediction of extent and severity of coronary artery disease. Conclusion: We concluded that the clinical entity of CHD should be differentiated from its underlying pathologicprocess, coronary atherosclerosis, and so should be CHD risk factorsdistinguished from the risk factors for development of atherosclerosis.Different reasons can be given for the absence of significant associations between important risk factors and extent or severity of disease.For psychological risk factors in particular, a multistage developmentof CHD with the potential for different risk factors involvement atdifferent stages, is the best explanation. Most probably, psychological riskfactors are involved in acute and sudden deteriorations in coronary flow due to coronary vasoconstriction or spasm, which makes them more important in the secondary rather than the primary prevention of coronary heart disease.
Keywords: coronary angiography; coronary disease; dejavniki tveganja; koronarna angiografija; koronarna bolezen; preprečevanje; prevention; risk factors